PENGARUH MANAJEMEN LABA,RISIKO PASAR DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PASAR - Nanda Stefany Mahadewi, 12.05.52.0240; Susilowati, Yeve (Students Journal of Accounting and Banking, 2014)
This study was conducted to determine the effect of earnings management, market risk and ownership structure of the market value. Testing identified using an accrual earnings management, market risk with beta and institutional ownership structure. This research was conducted at the manufacturing company, the data obtained from the audited financial statements in IDX and ICMD 2009 to 2012. Data collection using purposive sampling method. From the results of research conducted by multiple linear regression analysis method is known that earnings management and ownership structure has no significant effect on the market value while the market risk of a significant effect on the market value.Keywords: Earning Management, market risk, ownership, market value